2004
DOI: 10.1111/j.1365-2702.2004.00953.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure ulcer prevention in nursing homes: views and beliefs of enrolled nurses and other health care workers

Abstract: Background.  In the Netherlands much attention has been paid to pressure ulcer prevention. National guidelines on pressure ulcer prevention were developed in 1985 and adapted in 1992 at the request of a national organization for quality assurance in health care. Several studies indicate that nurses seem to be insufficiently informed about pressure ulcer preventive activities. There is, however, no information available about the reasons why nurses seem to be insufficiently informed. Aims and objectives.  This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 23 publications
3
43
0
8
Order By: Relevance
“…With adequate policy and management, awareness among health care organizations of the need to reduce the prevalence of pressure ulcers will hopefully affect the level of awareness among their staff. However, based on the present study and the research by Buss et al [23], which found that nurses do not seem to have the intention to change their preventive actions, we recommend further research to study which tailored approach would help change nurses' knowledge, beliefs and performance regarding pressure ulcer prevention. Potentially useful interventions in this respect include education and refresher courses for nurses in the context of a comprehensive approach.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…With adequate policy and management, awareness among health care organizations of the need to reduce the prevalence of pressure ulcers will hopefully affect the level of awareness among their staff. However, based on the present study and the research by Buss et al [23], which found that nurses do not seem to have the intention to change their preventive actions, we recommend further research to study which tailored approach would help change nurses' knowledge, beliefs and performance regarding pressure ulcer prevention. Potentially useful interventions in this respect include education and refresher courses for nurses in the context of a comprehensive approach.…”
Section: Discussionmentioning
confidence: 51%
“…Pieper and Mott [21] showed that registered nurses had insufficient knowledge about pressure ulcers, and Panagiotopoulou and Kerr [22] showed that nurses' average level of agreement with expert opinion regarding the value of preventive measures was a mere 50%. Despite the publication of research findings that support the importance of using evidence-based guidelines, studies have found that guidelines are frequently not implemented and nurses' performance is often based on intuition, experience or habit [23-25]. …”
Section: Introductionmentioning
confidence: 99%
“…The compliance of nurses to the guidelines was found to be influenced by several barriers [11,12]. A lack of knowledge is an apparent barrier for using the guidelines in clinical practice [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…The differences between the countries regarding these top-five interventions might be due to a higher awareness of the relevance of the process and steps of implementation in Dutch hospitals and nursing homes than in German and Austrian settings because of the longer history of nursing science in The Netherlands. Furthermore, The Netherlands started to develop national guidelines, for example, for pressure-ulcer prevention and treatment, as early as 1985 [66], whereas, in Germany, this process was started in 1999 with the development of expert standards (a type of guideline) [67], and education as the recommended implementation intervention [68]. In Austria, there exists no equivalent institution on a national level which is responsible for the development of national guidelines for relevant care problems in nursing.…”
Section: Discussionmentioning
confidence: 99%